Istijabatu Thalabah Qismi Ta’līm al-Lughah al-‘Arabiyah ‘ala Ta’lim Maharah al-Kalam bi Istikhdami Google Meet bi Jami’ah Al-Raniry - Saputra, Hadi; Urrahmah, Nisa; Hilmi, Danial (Al-Wazan: Journal of Arabic Education, 2023)
The learning process during the Covid-19 pandemic was implemented with an online system, this made lecturers able to develop learning activities effectively using various technologies, one of which was the use of video conferences in the form of the Google Meet application. This prompted this research to explore student responses to the use of Google Meet in speaking skill learning. This study uses a descriptive quantitative approach at UIN Ar-Raniry Aceh through data collection using a questionnaire, while the analytical technique used is descriptive statistics. This study shows that as many as 51% of students disagree with the use of Google Meet in learning speaking skill, and 49% of students agree with the use of Google Meet in speaking skill learning. The findings of this study indicate that learning maharah kalam using Google Meet is still not favored by students, so it becomes a challenge for lecturers to develop online learning for the better. This study recommends further research to test the effectiveness of Google Meet on student motivation or learning achievement.